The Relationship between Healthy Life Behaviour (Knowledge, Attitude, and Practice) with the Occurrence of Scabies in IMMIM Putra Islamic boarding school Makassar: The Occurrence of Scabies - Endang sri mulyawati Liambana; Firnasrudin Rahim; Nur Juliana; Muhammad Hosni Mubarak (Journal of sciences and health, 2021)
Background: Scabies as a neglected tropical disease, this disease was characterized by symptoms of itching at night due to higher activity of mites in humid and hot temperatures. According IACS, an incidence of scabies varies from 0,3% to 46%. This study was conducted to determine the relation between healthy behavior which consist of knowledge, attitudes, and practices with occurance of scabies in IMMIM Putra islamic boarding school Makassar Method: This type of research used an analytic observational method with a cross sectional study design. Research respondents were taken by purposive sampling and obtained 100 respondents. Data collection is done by filling out questionnaires. The data were analyzed by chi square test Results: The results showed that 50,0% scabies positive and 50,0% non-scabies from class VIII and IX. Analysis of bivariate found a significant relationship between knowledge (p value = 0,001) with the incidence of scabies and there was no relationship between attitudes (0,092), actions in the form of personal hygiene (0,534) and habits (0,110) with the incidence of scabies  IMIM Putra Islamic boarding school  Makassar Conclusions: It is necessary to make effective and efficient promotive efforts to overcome the incidence of scabies such as promotion, counseling and health education about scabies; provide facilities for students such as open clotheslines, clothes storage and a place to hang clothes Keywords: Scabies, knowledge, attitude, personal hygiene and habits